Analysis and the Comparative Study of the Critical and Creative Process in the Poetry of T. S. Eliot - Yadav, Manoj Kumar; Yadav, Meenakshi Sharma (International Journal of Psychosocial Rehabilitation, 2020)
The subject of this paper is to investigate the creative and critical process in the poetry of T. S. Eliot systematically. There are some sardonic undercurrents that can be seen running through Eliot’s poetry which have an analytical as well as a creative process. A detailed reference comparative study has been underpinned to the poems of Wordsworth’s “Composed upon Westminster Bridge”, John Keats’s “Ode to a Nightingale”, Arthur Mizener’s “To Meet Mr. Eliot”, W. B. Yeats’s “The Lake Isle of Innisfree” and “The Second Coming”, F. R. Leavis’s “The Significance of the Modern Waste Land”, and Allen Tate’s “On Ash Wednesday”, have also been referred in which the creative and critical process has been critically analyzed with the selected poems of T. S. Eliot for their scientific discourse analysis.